Comparative analysis of safety management systems and safety culture in aircraft maintenance - Corrigan, Siobhán (Trinity College (Dublin, Ireland). School of Psychology, 2003)
The overall objective of the thesis was on developing a deeper understanding of the organisational processes of safety management systems and how they are embedded in the culture of aircraft maintenance organisations. The thesis has developed and validated a comprehensive model of safety management that is linked to the wider cultural context of organisations. The model highlights the ability of organisations to establish strategies, goals and internal standards; to plan and organise production to an optimal standard; to determine what actually happens in practice; to monitor and adjust systems and procedures and to learn from recommendations.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin